Adverse Juvenile Probation Supervision Outcomes: Noncompliance, Revocation, and Failure to Appear at Review Hearings - NeMoyer, Amanda (Criminal justice and behavior, 2020)
Despite widespread use of community-based supervision for justice-involved youth, little research has examined what might contribute to youth performance under supervision. A recent investigation of probation practices in one jurisdiction noted that failure to appear at a review hearing was strongly associated with probation revocation. To determine whether these findings would replicate elsewhere and to identify youth characteristics and behaviors significantly related to failure to appear at review hearings, the current study examined probation records for 200 youth under supervision in another large mid-Atlantic county. Some similarities between jurisdictional findings arose, but notable differences were also observed. For instance, results revealed significant relationships between youth “absent without leave” status and two outcomes: failure to appear at the next hearing and probation revocation at their next hearing appearance. Findings further develop existing understanding of youth performance under supervision and suggest potential avenues for further investigation and future intervention.